ANTIMICROBIAL SCREENING OF THE LEAF EXTRACTS OF BACOPA MONNIERI (L) PENNELL - Verma, Maya (International Journal of Current Pharmaceutical Research, 2016)
Objective: To investigate the antibacterial efficacy of leaves of Bacopa monnieri (L.) Pennell Methods: The present study evaluates the anti-microbial activity of Bacopa monnieri against selected bacterial strains (E. coli, E. coli K 88,Klebsiella pneumoniae, Proteus vulgaris, Bacillus subtilis UC 564,B. pumilus 8241,B. licheniformis, Staphylococcus aureus ATCC 6571,Streptococcus faecalis 52,Enterococcus faecalis ATCC 29212,Pseudomonas aeruginosa, Salmonella typhii 62,Shigella dysenteriae 3,S. flexneri E0 3429,S. sonnei E0 8869) and fungal cultures of Aspergillus niger and candida albicans using disc diffusion assay. Results: Methanol extract has maximum (24±0.5) inhibitory effect against Staphylococcus aureus ATCC 6571 at a concentration of 15 mg/ml,which is followed by Streptococcus faecalis 52 (22±0.0) and Klebsiella pneumoniae (22±0.2) at the same concentration. Conclusion: The results showed maximum antifungal activity against C. albicans which was followed by A. niger.